Wastewater and sludge management and research in Oman: An overview. (4th March 2017) - Jaffar Abdul Khaliq, Suaad; Ahmed, Mushtaque; Al-Wardy, Malik; Al-Busaidi, Ahmed; Choudri, B.S.
ABSTRACT: It is well recognized that management of wastewater and sludge is a critical environmental issue in many countries. Wastewater treatment and sludge production take place under different technical, economic, and social contexts, thus requiring different approaches and involving different solutions. In most cases, a regular and environmentally safe wastewater treatment and associated sludge management requires the development of realistic and enforceable regulations, as well as treatment systems appropriate to local circumstances. The main objective of this paper is to provide useful information about the current wastewater and sludge treatment, management, regulations, and research in Oman. Based on the review and discussion, the wastewater treatment and sludge management in Oman has been evolving over the years. Further, the land application of sewage sludge should encourage revision of existing standards, regulations, and policies for the management and beneficial use of sewage sludge in Oman. Implications : Wastewater treatment and sludge management in Oman have been evolving over the years. Sludge utilization has been a challenge due to its association with human waste. Therefore, composting of sewage sludge is the best option in agriculture activities. Sludge and wastewater utilization can add up positively in the economic aspects of the country in terms of creating jobs and improving annual income rate. The number of research projects done on wastewater reuse and other ongoing ones related to the land application of sewage sludge should encourage revision of existing standards, regulations, and policies for the management and beneficial use of sewage sludge in Oman.